2018
DOI: 10.1101/gad.316810.118
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic turnover of paused Pol II complexes at human promoters

Abstract: Paused RNA polymerase II (Pol II) that piles up near most human promoters is the target of mechanisms that control entry into productive elongation. Whether paused Pol II is a stable or dynamic target remains unresolved. We report that most 5' paused Pol II throughout the genome is turned over within 2 min. This process is revealed under hypertonic conditions that prevent Pol II recruitment to promoters. This turnover requires cell viability but is not prevented by inhibiting transcription elongation, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 77 publications
11
91
0
Order By: Relevance
“…Interestingly, work from a number of laboratories has highlighted that the stability of paused Pol II can differ substantially among genes (Buckley et al, 2014;Chen et al, 2015;Erickson et al, 2018;Henriques et al, 2013;Krebs et al, 2017;Shao and Zeitlinger, 2017). In particular, recent studies of paused Pol II in Drosophila revealed a surprising diversity of behaviors following treatment of cells with Triptolide (Trp), an inhibitor of TFIIH that prevents new transcription initiation (Henriques et al, 2018;Krebs et al, 2017;Shao and Zeitlinger, 2017;Vispé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, work from a number of laboratories has highlighted that the stability of paused Pol II can differ substantially among genes (Buckley et al, 2014;Chen et al, 2015;Erickson et al, 2018;Henriques et al, 2013;Krebs et al, 2017;Shao and Zeitlinger, 2017). In particular, recent studies of paused Pol II in Drosophila revealed a surprising diversity of behaviors following treatment of cells with Triptolide (Trp), an inhibitor of TFIIH that prevents new transcription initiation (Henriques et al, 2018;Krebs et al, 2017;Shao and Zeitlinger, 2017;Vispé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be explained by recent experiments, including live imaging in vivo which showed that most 5' bound Pol II is rapidly turned over (Erickson et al 2018;Kamieniarz-Gdula and Proudfoot 2019;Steurer et al 2018) This could be associated with cycles of abortive initiation rather than stable pausing. Over time, such transiently associated Pol II may be detected by ChIP but would not necessarily produce scaRNAs which require transcriptionally engaged Pol II.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that regulated Pol II pausing is a ubiquitous mechanism to control gene expression which relies on a stably paused Pol II complex which can be acted on to cause pause release (Adelman and Lis 2012;Jonkers, Kwak, and Lis 2014;Jonkers and Lis 2015;Rahl et al 2010). However, recently it has also been suggested that the high density of Pol II as revealed by ChIP-seq may reflect a dynamic process of premature termination (Erickson et al 2018). This is supported by in vivo imaging studies which reveal the majority of Pol II is associated with chromatin for seconds (Steurer et al 2018) and modeling which revealed that the turnover of Pol II on housekeeping genes was comparable to highly "paused" genes such as HSPA1 (Krebs et al 2017).…”
Section: Differential Gene Expression Is Predominantly Regulated Via mentioning
confidence: 99%
“…Promoter-proximal transcriptional pausing has recently been linked to premature termination in metazoans (Chiu et al, 2018;Erickson et al, 2018;Krebs et al, 2017;Steurer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Here, premature termination and exosome-dependent degradation of mRNA transcripts for a large class of protein-coding genes has been recently described to coincide with promoter-proximal RNAPII pausing sites (Chiu et al, 2018). Experiments with chemical transcriptional inhibitors indicated high rates of turnover and premature termination of promoter-proximal paused RNAPII (Erickson et al, 2018;Krebs et al, 2017;Steurer et al, 2018), suggesting regulation of gene expression by transcriptional attenuation. Furthermore, several studies in higher organisms have reported that production of short, promoter-proximal transcripts is associated with RNAPII pausing and backtracking, and it has a role in regulation of gene expression (reviewed in (Yu et al, 2018)).…”
Section: Introductionmentioning
confidence: 98%